Nutrient limitation or home field advantage: does microbial community adaptation overcome nutrient limitation of litter decomposition in a tropical peatland? - Hoyos-Santillan, Jorge; Lomax, Barry H.; Turner, Benjamin L.; Sjögersten, Sofie (Wiley, 2018)
Litter decomposition is an important control on carbon accumulation in tropical peatlands. Stoichiometric theory suggests that decomposition is regulated by elemental ratios in litter while the home field advantage (HFA) hypothesis predicts that decomposer communities are adapted to local conditions. To date, the relative importance of these contrasting theories for litter decomposition and therefore the carbon balance of tropical peatlands remain poorly understood. We conducted two in situ litter decomposition experiments in a lowland tropical peatland. The first experiment tested the importance of the stoichiometric theory using a factorial nutrient addition experiment at two sites with contrasting vegetation (Raphia taedigera and Campnosperma panamensis) to assess how nutrient addition affected microbial enzyme activity and litter mass loss at the peat surface and at 50 cm depth. The second experiment tested the importance of HFA by reciprocal translocation of leaf litter from R. taedigera and C. panamensis forests, which differed in both litter chemistry and soil nutrient availability, to separate the influence of litter chemistry and soil/site properties on litter mass loss. The activities of hydrolytic enzymes involved in the decomposition of large plant polymers were stimulated by nitrogen addition only where nitrogen availability was low relative to phosphorus, and were stimulated by phosphorus addition where phosphorus availability was low. The addition of nitrogen, but not phosphorus, increased leaf litter decomposition under waterlogged conditions at 50 cm depth, but not at the peat surface. Decomposition was greatest for autochthonous litter irrespective of site nutrient status, indicating that adaptation of the microbial community to low nutrients can partly overcome nutrient limitation, and suggesting that HFA can influence litter decomposition rates. Synthesis. Our study shows that leaf litter decomposition and the activity of microbial enzymes in tropical peatlands are constrained in part by nutrient availability. However, such nutrient limitation of litter decomposition can be overcome by adaptation of the microbial community.